Investigating the involvement of potato (Solanum tuberosum L.) StPHR1 gene in the combined stress response to phosphorus deficiency and aluminum toxicity - Zhang, Feng; Wang, Wenlun; Yuan, Anping; Li, Qiong; Chu, Moli; Jiang, Sixia; An, Yanlin (Frontiers in Plant Science, 2024)
Phosphorus (Pi) deficiency and aluminum (Al) toxicity in acidic soils are important factors that limit crop yield. To further explore this issue, we identified 18 members of the StPHR gene family in the potato genome in this study. Through bioinformatics analysis, we found that the StPHR1 gene, an important member of this family, exhibited high expression levels in potato roots, particularly under conditions of Pi deficiency and Al toxicity stress. This suggested that the StPHR1 gene may play a crucial regulatory role in potato's resistance to Pi deficiency and Al toxicity. To validate this hypothesis, we conducted a series of experiments on the StPHR1 gene, including subcellular localization, GUS staining for tissue expression, heterologous overexpression, yeast two-hybrid hybridization, and bimolecular fluorescence complementation (BiFC). The results demonstrated that the StPHR1 gene is highly conserved in plants and is localized in the nucleus of potato cells. The heterologous overexpression of the gene in Arabidopsis plants resulted in a growth phenotype that exhibited resistance to both Pi deficiency and Al toxicity. Moreover, the heterologous overexpressing plants showed reduced aluminum content in the root system compared to the control group. Furthermore, we also identified an interaction between StPHR1 and StALMT6. These results highlight the potential application of regulating the expression of the StPHR1 gene in potato production to enhance its adaptation to the dual stress of phosphorus deficiency and high aluminum toxicity in acidic soils.